2017
DOI: 10.1186/s13019-017-0636-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative liver dysfunction on cardiac surgery outcomes

Abstract: BackgroundTo determine the impact of preoperative Liver Dysfunction (LD) on outcomes after elective Coronary Artery Bypass Grafting (CABG) and Valvular surgery (VS).MethodsThe Nationwide Inpatient Sample (2002–2010) was queried to identify patients with LD who had elective CABG or VS utilizing ICD-9-CM diagnosis and procedure codes. These patients were matched with the similar patients without LD (controls) by propensity score matching. Chi-square and Wilcoxon rank sum tests were used for analysis.ResultsWe id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 15 publications
(21 reference statements)
1
20
0
Order By: Relevance
“…Potentially as a consequence of increased rates of postoperative complications, existing literature consistently reports longer in-hospital and ICU stays and greater healthcare expenditure in cirrhotic patients. [30][31][32] This was reaffirmed by our study with a matched control cohort by recording significantly longer in-hospital and ICU stays, prolonged mechanical ventilation, and increased requirement for renal replacement therapy in cirrhotic patients compared with non-cirrhotic controls. Several studies have shown that factors such as Euroscore, MELD, central venous pressure, and CABG status were independently associated with increased mortality in cirrhotic patients undergoing cardiac surgery.…”
Section: Key Findingssupporting
confidence: 72%
“…Potentially as a consequence of increased rates of postoperative complications, existing literature consistently reports longer in-hospital and ICU stays and greater healthcare expenditure in cirrhotic patients. [30][31][32] This was reaffirmed by our study with a matched control cohort by recording significantly longer in-hospital and ICU stays, prolonged mechanical ventilation, and increased requirement for renal replacement therapy in cirrhotic patients compared with non-cirrhotic controls. Several studies have shown that factors such as Euroscore, MELD, central venous pressure, and CABG status were independently associated with increased mortality in cirrhotic patients undergoing cardiac surgery.…”
Section: Key Findingssupporting
confidence: 72%
“…Moreover, operations for hepatocellular carcinoma (HCC) in patients with liver cirrhosis and portal hypertension are considered difficult and may be associated with relatively high morbidity [ 12 ]. It has been proved that patients with liver cirrhosis have worse overall outcomes and a higher perioperative complication rate [ 13 , 14 ].…”
mentioning
confidence: 99%
“…Another strategy is to simply stratify by presence of any liver disease, which has been shown in the national inpatient sample to dramatically increase rates of mortality and other complications. [23] In this analysis liver disease was a very strong independent predictor of operative mortality with an adjusted odds ratio of 2.08 (p<0.0001). Also consistent with prior results liver disease was independently associated with major morbidity (AOR 1.36, p=0.003).…”
Section: Commentmentioning
confidence: 57%